A Prospective Study of Emerging Women Micro Entrepreneur COVID-19 With Reference to Northwest Delhi (International Journal of Innovative Research in Engineering & Management, 2021)
The COVID-19 pandemic crisis in 2020 had a significant  influence on women entrepreneurs' commercial activity.  Changes in the scope, style, and structure of business in most  small or medium firms, including those owned or managed by  women, have been impacted by pandemic protection measures  implemented to limit health hazards or the adoption of new  restrictions. The goal of the study was to obtain insight into the  impacts of the pandemic on women's companies as well as  balancing business or family duties of women entrepreneurs in  the altered conditions since prior research had shown that  women bore the brunt of the crisis. The study was carried out  using an online survey with a total of 93 participants (women  entrepreneurs in Delhi). The findings revealed that the COVID 19 pandemic harmed 78 percent of women-owned businesses  and that women compensated for the loss of hours spent at work  by working at home and caring for family members. Owning a  company may provide women with the independence they want  as well as the economic and social success they need. On a  national level, business ownership is crucial for future  economic progress.
Keywords: COVID-19 Pandemic; COVID-19; Companies; Entrepreneur; Women